Supervised mHeath Exercise Improves Health Factors More Than Self-Directed mHealth Exercise: A Clinical Controlled Study - Hu, Yukun; Zhang, Yong; Qi, XiaoYa; Xu, XiaoYang; Rahmani, Jamal; Bai, Ruixue; Mei, Ying (Frontiers in Public Health, 2022)
Wearable physical activity trackers are getting popular for the self-management of weight despite limited evidence of their efficacy. Studies have proven that on-site supervised exercise is superior to unsupervised exercise for many health problems, there is no evidence comparing the effectiveness of remote supervision exercise with self-directed exercise based on mHealth. This study aims to compare the effects of mHealth-based supervised exercise to mHealth-based self-directed exercise on weight control in the overweight and obese population. A nonrandomized controlled clinical study was conducted. Overweight or obese volunteers were given personalized exercise prescriptions based on their HRR (Heart Rate Reserve), all patients were equipped with wearable heartbeat trackers to follow their exercise performance and additional remote supervisions were added to the intervention group. Exercise performances, weight losses, and health examinations were compared between 2 groups after 12 weeks of follow-up. Analysis of covariance (ANCOVA) was used to determine any differences between study groups after intervention. Two groups had the same rate of attrition in 12 weeks of follow-up, but the exercising day, the effective exercising day and the rate of effective exercising day in the supervised group were higher than those in the control group. Weight loss was −2.7 ± 2.8 kg in the intervention group and −2.0 ± 2.9 kg in the control group (P = 0.23). Compared with the control group, participants in the intervention group improved their liver function, kidney function, fasting blood sugar, total cholesterol, and triglyceride. mHealth-based supervised exercise is more effective in health factors improvement than mHealth-based self-directed exercise among overweight and obesity participants.